2013
DOI: 10.4209/aaqr.2012.10.0274
|View full text |Cite
|
Sign up to set email alerts
|

Urban Boundary Layer Height Characteristics and Relationship with Particulate Matter Mass Concentrations in Xi’an, Central China

Abstract: The characteristics of the planetary boundary layer height (PBLH) and the relationship between PBLH and particular matter (PM) mass concentration in Xi'an, central China, are analyzed in this study. Three PBLH calculation methods are used in this study, namely the Holzworth, Liu, and Nozaki approaches. The daily minimum and maximum PBLHs are determined by the Holzworth method, the hourly PBLHs are calculated by the Nozaki method, and the results of the Nozaki method are evaluated by the Liu method. The PBLH ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(45 citation statements)
references
References 27 publications
2
40
1
Order By: Relevance
“…Some previous studies Zhao et al 2009) outside of the LUR framework have demonstrated that meteorological factors have a significant impact on PM 2.5 diurnal cycle in Beijing. Our models of peak and non-peak hours were driven by the same explanatory variables and produced similar patterns of PM 2.5 concentrations, which is more likely to be interpreted by meteorological factors and boundary layer height (Du et al 2013) instead of specific sources such as traffic emission and cooking. In addition, the models of peak hours did not include more traffic variables, which might also be explained by the secondary nature of PM 2.5 .…”
Section: Diurnal Variationsmentioning
confidence: 79%
“…Some previous studies Zhao et al 2009) outside of the LUR framework have demonstrated that meteorological factors have a significant impact on PM 2.5 diurnal cycle in Beijing. Our models of peak and non-peak hours were driven by the same explanatory variables and produced similar patterns of PM 2.5 concentrations, which is more likely to be interpreted by meteorological factors and boundary layer height (Du et al 2013) instead of specific sources such as traffic emission and cooking. In addition, the models of peak hours did not include more traffic variables, which might also be explained by the secondary nature of PM 2.5 .…”
Section: Diurnal Variationsmentioning
confidence: 79%
“…The size-resolved dN T / dlogD a for each individual month exhibited a consistent and flat concentration profile at < 1 µm. Previous studies where a similar instrument was used have reported that pronounced diurnal variations in N T are strongly coupled with diurnal variations in meteorological variables, especially mixing layer depth Raatikainen et al, 2014;Du et al, 2013). The ab- sence of pronounced diurnal variations in N T at this particular site may be a result of weak dependence of coarse-mode TAP concentrations on meteorological parameters combined with persistent rainfall causing the washout of these particles (Radke et al, 1980;Raatikainen et al, 2014;Kanawade et al, 2014;Shika et al, 2016).…”
Section: Diurnal Patternsmentioning
confidence: 99%
“…Studies relying on numerical parameterizations were conducted by Tiwari et al (2014), who used reanalysis data, and Du et al (2013), who used routine meteorological observations to find an anticorrelation between PM 2.5 and MLH for Delhi, India, and Xi'an, China. Rost et al (2009) found a strong anticorrelation between PM 10 and MLH (derived from radiosonde data) for Stuttgart, Germany, with a coefficient of determination of R 2 > 0.95.…”
mentioning
confidence: 99%